HAK ISTRI NON MUSLIM TERHADAP HARTA PENINGGALAN SUAMI YANG BERAGAMA ISLAM: STUDI KASUS PUTUSAN PENGADILAN AGAMA MAKASSAR NO. 732/PDT.G/2008, PUTUSAN PENGADILAN TINGGI MAKASSAR NO. 59/PDT.G/2009 DAN PUTUSAN MAHKAMAH AGUNG NO 16 K/AG/2010 - Sufiati, Dian; Anggraeni, Ria Dwi (E-Journal Widya Yustisia, 2017)
The heteroqenity of Indonesian communities bring along mixed marriage, namely the marriage among those of diferrant religions. Such marriaqes are reqistered at the office of Civil Affairs.There exists some disputes betwean those of Moslem husband and non Muslem wive after the husband’s death concerning the family heritege. The purpose of this writing is to analyze the non moslem’s wife status in relation to the death husband who is a Moslem.The try to analyze such issue has been related to the legal consideration of the Supreme’s Court decision No. 16K/AG/2010 regarding the disute berween the late Moslem’s husband and his wife, who is a non-Moslem. The method used is normative juridical, the data was qained from library research, which have been procrssed and analyzed qualitatively. The result of this research indicated that the status of a non-moslem wife is not acknowledged by the teaching of the Al-Qur’an, Haditz and Islamic law compilation. But the Supreme Court declared such tradition as nuli and void by means of the Decision No. 16K/AG/2010. Such decision stipulated that any and all Non-Moslem wife has the riqht to get her portion from her late husbands’s haritage. The basic consideration of Supreme Court’s cedision is that the said wife has lived together sincerely with her husband until the time her husband passet away. The Supreme Court has to explain such decision to diverse communities in Indonesia, so that such decision qained its force.